(untitled) (Birat Journal of Health Sciences, 2025)
Introduction : Pregnancy is a physiological condition associated with numerous systemic changes across the trimesters. The respiratory system undergoes significant alterations due to mechanical factors, hormonal influences and activity-related needs of the mother and also driven by the increasing metabolic demands of the developing fetus. Objectives: The objective of this study was to assess the normal values of commonly used pulmonary function parameter (PFT) across different trimesters of pregnancy and to compare it with normal. Methodology: It was a longitudinal study to assess the pulmonary function test for the pregnant women (experiment, E) at different trimester and was compared with age, height and weight matched non-pregnant women (control, C). Convenient, purposive sampling technique was employed to collect the data for pregnant (Experiment=76) and non-pregnant women (Control=76) attending the obstetrics and gynecology department of Nobel Medical College and teaching hospital (NMCTH). Ethical clearance was granted by ethical review committee of NMCTH. SPSS version 24 was used for descriptive analysis of all variables and one-way ANOVA (Post Hoc) to compare the means of pulmonary function test. Results: The mean age (E=32±3.77, C= 32.47±4.30, p=0.471)), height (E=1.58±.02, C= 1.57±.02, p=0.131), weight (E=56.81±1.04, C=56.67±1.06, p=.440) were analyzed which was non-significant. Tidal volume (TV) and respiratory rate (RR) significantly increased (p<0.001). Inspiratory reserve volume (IRV), expiratory reserve volume (ERV), peak expiratory flow rate (PEFR), oxygen saturation (SO2) significantly decreased (p<0.001). Forced vital capacity (FVC), Forced expiratory volume in 1st second (FEV1) and FEV1/FVC decreases non-significantly (p>0.05). Conclusions: Assessing PFT parameters across different trimester of pregnancy and comparing with non-pregnant women reported significant difference.